Understanding performance ratings: Dynamic performance, attributions, and rating purpose - REB, Jochen (Institutional Knowledge at Singapore Management University, 2010)
The present two studies integrate and extend the literatures on dynamic performance, performance attributions, and rating purpose, making several important contributions. First, examining attributions of dynamic performance, Study 1 predicted that performance mean and trend would affect judged ratee ability and effort and that performance variation would affect locus of causality; both predictions were supported by the results. Second, investigating the interaction between dynamic performance and rating purpose. Study 2 predicted that performance mean would have a stronger impact on administrative than on developmental ratings, whereas performance trend and variation would have a stranger impact on developmental than on administrative ratings; again, both predictions were borne out by the results. Third. both studies found that performance trend interacted with performance mean and variability to predict overall ratings. Fourth, both studies replicated main effects of dynamic performance characteristics on ratings in a different culture and, in Study 2, a sample of more experienced managers.